Performa Ayam Ras Petelur pada Letak Cage Berbeda dalam Sistem Closed House di Global Buwana Farm - Amijaya, D. T.; Yani, A.; Rukmiasih, Rukmiasih (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
Air flow distribution, temperature, and humidity in the cage will differ from the inlet to the outlet. Microclimate difference in the cage at the inlet to the outlet can affect the production and quality of the eggs produced. The purpose of this research was to study the performance of laying hens on different location of cage (inlet, middle and outlet) in closed house system. In total 36 Lohmann hens were placed in each treatment including cage inlet, middle, and outlet. Traits measured were productive performance (hen day performance and egg weight) and egg qualities (haugh unit and egg shell thickness). The data were be analyzed using anova, tukey test, pearson correlation coefficient and completely randomized design. Result showed that here was very significant different on different location cage between temperature, relative humidity, and wind velocity. Cage inlet resulted better performance of laying hens compared to the middle and outlet cage.